2020
DOI: 10.1007/s42965-020-00099-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of the first groups of collared peccaries (Pecari tajacu) reintroduced in South America

Abstract: The collared peccary (Pecari tajacu) is distributed from southwestern USA to northern Argentina; however, in some Argentinean localities it went extinct over 50 years ago. As part of a rewilding project, two peccary groups (one captive-bred family group and one mixed group formed by not genetically related individuals) were reintroduced to the Ibera National Park. Following the release, we monitored the movements of 16 individuals to obtain GPS locations every 100 min, for 6 months. We evaluated the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…A diurnal activity pattern for collared peccaries was also observed in a study conducted at the Sonora desert (Arizona, USA), but only in the months with mild temperatures; in months with higher temperatures, collared peccaries showed a more cathemeral pattern of activity (Bigler, 1974). In Argentina, a group of reintroduced collared peccaries showed a diurnal activity pattern throughout the year independently of the temperature (Hurtado et al, 2018), a pattern similar to the one found in the present study. Thus, it seems that collared peccaries' activity patterns vary depending on the study area and that some characteristics, like the climate, can influence these patterns.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A diurnal activity pattern for collared peccaries was also observed in a study conducted at the Sonora desert (Arizona, USA), but only in the months with mild temperatures; in months with higher temperatures, collared peccaries showed a more cathemeral pattern of activity (Bigler, 1974). In Argentina, a group of reintroduced collared peccaries showed a diurnal activity pattern throughout the year independently of the temperature (Hurtado et al, 2018), a pattern similar to the one found in the present study. Thus, it seems that collared peccaries' activity patterns vary depending on the study area and that some characteristics, like the climate, can influence these patterns.…”
Section: Discussionsupporting
confidence: 89%
“…Among the Tayassuidae, the collared peccary is the species capable of occupying the greatest diversity of habitats, from humid forests to semi‐arid regions, including environments altered by human activities, except those that are extremely altered (Sowls, 2013). Collared peccary home range varies from 150 to 250 ha (Hurtado et al., 2018; Judas & Henry, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled sport hunting and the reduction of forested areas are among the leading causes of its disappearance. Lastly, the collared peccary ( Pecari tajacu ) is involved in reintroduction programs ( 14 , 19 ) and is also classified as a threatened species, with its primary threat being hunting ( 17 ).…”
Section: Introductionmentioning
confidence: 99%